Predicting Marital Stability Among Divorcing Couples in Ilam Based on Social Networksiin Marital Relationships - Nadi, Zahra; Mami, Shahram; Ahmadi, Vahid; Sayemiri, Korosh (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective:  This study aims to explain the relationship between social networks in marital relationships and ADHD with marital stability among divorcing couples in Ilam.Methods and Materials: The research is applied in terms of purpose and employs a descriptive-correlational method. The statistical population of this study includes all divorcing couples in Ilam who visited family courts, counseling centers, and divorce registration offices during 2019-2020. The sampling method used in this study was convenience sampling, selecting 351 individuals meeting the inclusion criteria as participants. Given the nature of the study, data were collected using a researcher-designed questionnaire on social networks in marital relationships and the Marital Instability Questionnaire by Edwards et al. (1987). Data analysis involved descriptive and inferential statistics. Descriptive statistics were used to calculate frequency, percentage, mean, and standard deviation, while the Kolmogorov-Smirnov test was applied to ensure data normality. Inferential statistics, including correlation coefficients and multivariate regression analysis, were conducted using SPSS 22 software.Findings: The findings indicated a correlation coefficient of 0.860 between social networks in marital relationships and marital stability among divorcing couples in Ilam. The coefficient of determination was calculated as 0.739, indicating that 73.9% of the changes in marital stability among divorcing couples in Ilam can be attributed to social networks in marital relationships.Conclusion:  The findings highlight the significant role of social networks and subjective norms in marital stability, emphasizing their predictive value within the investment model framework for divorcing couples in Ilam.